Peran Sholat dalam Membangun Kesadaran Religius Umat Muslim - Septiadi Septiadi; Utari Binasetiaty Nurhidayani; Ainun Zahra; Koko Koko (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Prayer (ṣalāh) holds a central and indispensable place within the Islamic faith as one of the most fundamental acts of devotion. This study is designed to investigate the extent to which salah contributes to the formation and strengthening of religious consciousness among Muslims, as manifested in changes to individual attitudes, conduct, and discipline in everyday life. Employing a qualitative design grounded in library-based research, this study draws on primary Islamic sources, including the Qur'an and prophetic traditions, alongside relevant contemporary scholarly works. The findings reveal that the consistent practice of salah, carried out with sincerity and mindfulness, plays a meaningful role in cultivating spirituality, deepening the bond between humanity and the Creator, and fostering conduct that aligns with Islamic values. Moreover, salah is demonstrated to serve as an effective mechanism for self-regulation, discouraging unethical behavior while enhancing individual moral character. In conclusion, salah transcends its ritual dimension to function as a vital and holistic instrument for building comprehensive religious consciousness in the daily lives of Muslims.